The RBE in ion beam radiotherapy: in vivo studies and clinical application - Karger, Christian; Glowa, Christin; Peschke, Peter; Kraft-Weyrather, Wilma (Zeitschrift für medizinische Physik, 2021)
Ion beams used for radiotherapy exhibit an increased relative biological effectiveness (RBE), which depends on several physical treatment parameters as well as on biological factors of the irradiated tissues. While the RBE is an experimentally well-defined quantity, translation to patients is complex and requires radiobiological studies, dedicated models to calculate the RBE in treatment planning as well as strategies for dose prescription. Preclinical in vivo studies and analysis of clinical outcome are important to validate and refine RBE-models. This review describes the concept of the experimental and clinical RBE and explains the fundamental dependencies of the RBE based on in vitro experiments. The available preclinical in vivo studies on normal tissue and tumor RBE for ions heavier than protons are reviewed in the context of the historical and present development of ion beam radiotherapy. In addition, the role of in vivo RBE-values in the development and benchmarking of RBE-models as well as the transition of these models to clinical application are described. Finally, limitations in the translation of experimental RBE-values into clinical application and the direction of future research are discussed.